PEMBELAJARAN BERBANTUAN FACEBOOK UNTUK MENINGKATKAN HASIL BELAJAR - Retno Widyaningrum (Perspektif Ilmu Pendidikan, 2013)
The advancement of information and communication technology (ICT) has affected the educational practices including instructional process. In Indonesia, ICT has been benefitted for instructional purposes, one of them is social net Facebook. This research aimed at revealing how facebook can be used to improve the students’ learning achievement in the course of Innovation and Deffusion in Education (IDE) at The Curriculum and Educational Technology Departement, School of Education, State University of Jakarta. The research was conducted in the Even Semester of 2012 apllying survey method with all of IDE students as respondents. The data were collected and analyzed focusing on instructional design, prosess, and evaluation. The research findings concluded that facebook can facilitate learning to improve the students’ learning achievement.